Two-Dimensional Electroosmotic Consolidation Theory of Nonlinear Soil Voltage Distribution Characteristics - Yang Shen; Jianting Feng; Yinghao Ma; Hanlong Liu (Advances in Civil Engineering)
Soil voltage is generally assumed to show a linear relationship with distance from the cathode according to the established electroosmotic consolidation equation. However, this assumption is inconsistent with experimental results. To more reasonably reflect the soil consolidation process during electroosmosis treatment, it is necessary to consider the influence of the actual soil voltage distribution trend when establishing the electroosmotic consolidation equation. Electroosmosis results show that soil voltage exhibits nonlinear distribution characteristics against distance from the cathode. The change trend of soil voltage can be well reflected by cubic polynomial fitting. Then, the anodic electrode was taken as the research object, and a two-dimensional horizontal plane model of electroosmosis was established because it represents practical electroosmosis applications more closely than some other models. Based on this established model, the dissipation equation describing the excess pore water pressure and the soil consolidation equation were derived for the electroosmosis treatment process. The derivation process considered both linear and nonlinear soil voltage distributions, wherein the anode was closed and the cathode was open. Finally, the analytical solution was analyzed and validated with model test cases in terms of the excess pore water pressure and average moisture content of the soil. The trend observed in the measured excess pore water pressure was more consistent with that of the theoretical results calculated assuming a nonlinear soil voltage distribution than that obtained using a linear distribution. In addition, the measured values of the average moisture content in the soil were closer to the values calculated under a nonlinear distribution of soil voltage than to those calculated under a linear distribution. These results further show that the established consolidation equation is reasonable when a nonlinear distribution of soil voltage is considered. The proposed consolidation equation can thus improve the application of electroosmotic methods in the future.